밀러사이클 적용 스파크점화기관의 후기 흡기밸브 닫힘각 변화에 따른 연소성능 연구 - 정진호; J H Chung; 강선제; S J Kang; 김진수; J S Kim; 정석철; S C Jeong; 이진욱; J W Lee (한국분무공학회지, 2015)
In order to research engine characteristics of spark-ignited engine with intake valve closing timing change for Miller cycle, two cam for LIVC (Late Intake Valve Closing) were designed and fabricated an prototype valvetrain. And intake valve closing timing were adjusted to build low compressing and high expansion cycle for HEV. In experimental study, it were investigated with different engine speed, spark timing and air-fuel ratio to compare base cam and LIVC cam type. It was found that the volumetry efficiency and effective work of compression process were decreased in case of LIVC cam. When compared with the existing results, the maximum pressure in the cylinder was reduced about 12~13 bar and the volumetric efficiency was reduced about 16%.